Anti-candida activity by Hymenocallis littoralis extracts for opportunistic oral and genital infection Candida albicans - Jeevandran Sundarasekar; Geethaa Sahgal; Sreeramanan Subramaniam (Bangladesh Pharmacological Society, 2012)
Candida albicans is a unicellular fungus that causes an opportunistic infection in the oral cavity and vagina. The present article reports the inhibitory effects of Hymenocallis littoralis methanol sonication extracts against Candida albicans. This plant has been used widely in traditional medicine and has proven to possess anti-cancer properties for numerous cell lines. Various plant parts such as bulb, flower, anther, root, leaves and stem were tested against this opportunistic organism and found that the flower and anther were effective at 6.25 mg/mL. This is the first report on anti-candida activity of H. littoralis methanol extract. Transmission (TEM) and scanning electron microscope (SEM) observations were used to observe the cytological and morphological expression of the extract treated C. albicans. TEM reveal the complete destruction of nucleus and internal organelles in the yeast like fungus cell. SEM reveals the fissure on the membrane cells. The methanol crude extract has anti-candida activity for tested concentration.